Research on Decoration and Renovation Design of Old Ward Buildings in Hospitals - Lin, Fasheng (Journal of Progress in Civil Engineering, 2025)
In recent years, with the rapid development of China’s economy, the public’s demands for the quality of medical services have been increasing day by day. Due to outdated facilities and backward functions, the old hospital ward buildings are no longer able to meet the demands of modern medical care. This article focuses on the decoration and renovation design of old hospital ward buildings, deeply analyzes the necessity of the renovation, elaborates in detail on the principles that should be followed in the renovation design, and emphasizes a series of implementable, executable and referential renovation design strategies, covering multiple aspects such as spatial layout optimization, facility and equipment renewal, integration of humanized design, color and lighting design, environmental protection and safety considerations, It aims to provide useful references for improving the overall quality of the old hospital ward buildings and meeting the needs of patients and medical staff.